Part II: Simulation of 2009 global livable cities index and ranking of 2009 Asian livable cities index. - Lau, Priscillia Fong Ming. (2010)
This report is an extension of the Final Year Project “Part I: Ranking of 2009 Global Livable Cities Index” and attempts to apply the concepts and information from Part I. The objective of this study is to introduce and provide possible rankings using simulations based on dimensions of livability in accordance to the Global Livable City Index (GLCI) Framework. The simulation of the overall GLCI rankings will serve as a source of motivation for cities to channel more effort and resources into poor-performing areas.